Analysis of liquidity and profitability of general price level changes Applied Study State company for Glass and Ceramic industry - التميمي, عباس يحيى; حسين, عادل علي (Journal of Economics and Administrative Sciences, 2012)
The accountants are preparing the financial statements under the Monetary Unit Stability Assumption without taking into consideration the changement of prices for the monetary unit. The income statement accounts containing different items of expenses and revenues. These items are not paid or obtained at one date, because the value of monetary unit is changing from one date to another , also the financial position contains different items of current and fixed assets, also contains different items of long-term liabilities and ownership rights, the continuity of applying historical cost principle will make the financial statements misleading, The adoption of financial analyst of these statements will affects the results of the analysis because these ration do not reflect  the true financial situation of economic unity.